EVALUATION OF STUDENT CHARACTER EDUCATION PROGRAM KATOLIK WIDYA MANDIRA UNIVERSITY - Yustina Lawung (Yayasan Hurriah, Banda Aceh, 2023)
This study aims to analyze and determine the effectiveness of the implementation of student character education programs at Widya Mandira Catholic University in terms of context, input, process and product variables. This research includes evaluative research, which evaluates the implementation of learning programs. In this study, analyzing the effectiveness of implementing learning with the CIPP model (context, input, process and product). Respondents in this study were 150 students. Data was collected using questionnaires, interviews, observations, documents and APKG. Data were analyzed by descriptive analysis. To determine the effectiveness of implementing the student character education program, raw scores were transformed into Z then into T-Scores then verified into the Glickman prototype. In connection with the findings of this evaluative study, the results of the analysis of the context, input, process and product variables respectively show a value of (+ + +-), and if converted into the Glickman quadrant, the quality of the effectiveness of implementing student education programs at Widya Catholic University Mandira in 2021, classified as effective. To ensure that this program is more effective, the substance that needs to be refined is the product factor